Considerations for Treatment-free Remission in Patients With Chronic Myeloid Leukemia: A Joint Patient-Physician Perspective - Saglio, Giuseppe; Sharf, Giora; Almeida, Antonio; Bogdanovic, Andrija; Bombaci, Felice; Čugurović, Jelena; Deekes, Nigel; Garcia-Gutiérrez, Valentín; de Jong, Jan; Narbutas, Šarūnas; Westerweel, Peter; Zackova, Daniela (Clinical lymphoma, myeloma & leukemia, 2018)
Treatment-free remission (TFR) after discontinuation of tyrosine kinase inhibitor therapy is now an emerging treatment goal for patients with chronic myeloid leukemia, who have achieved a deep and stable response to treatment. Although guidance is now available, patients' questions regarding this progressive concept have yet to be addressed. The overall aim of this European Steering Group is a patient-centered approach that educates patients on their treatment options, including TFR, facilitates better patient-physician relationships, and meets patients' emotional and psychological needs. The present report outlines 5 key topic areas on discontinuing tyrosine kinase therapy and the implications of TFR for patient-physician consideration: what TFR is; when TFR is appropriate; which patients might and might not be eligible for TFR; and patients' considerations for discontinuing therapy, such as tyrosine kinase withdrawal syndrome, potential psychological implications, molecular recurrence, and repeat treatment. This Steering Group advocates that patients with chronic myeloid leukemia should have access to high-quality, frequent molecular monitoring and be treated in a specialist center with appropriate medical and psychological support. As patient concerns with attempting TFR become forefront in patient-physician discussions, a greater number of eligible patients might be willing to discontinue therapy.
Keywords: Patient Education as Topic; Physician-Patient Relations; inhibitory proteinkinas; nenasazení léčby; výsledek terapie; Neoplasm Recurrence, Local; Decision Making; kvalita života; lidé; Withholding Treatment; chronická myeloidní leukemie; vzdělávání pacientů jako téma; Treatment Outcome; míra přežití; Remission Induction; Protein Kinase Inhibitors; rozhodování; indukce remise; lokální recidiva nádoru; Survival Rate; vztahy mezi lékařem a pacientem; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Protein-Tyrosine Kinases; Quality of Life; tyrosinkinasy; Humans